Pathophysiology and transcriptomic analysis of Picea koraiensis inoculated by bark beetle-vectored fungus Ophiostoma bicolor - Liu, Ya; Zhou, Qinzheng; Wang, Zheng; Wang, Huiming; Zheng, Guiheng; Zhao, Jiaping; Lu, Quan (Frontiers in Plant Science, 2022)
Ophiostomatoid fungi exhibit a complex relationship with bark beetles; exhausting of host tree defenses is traditionally regarded as one of the key benefits provided to beetle vectors. Ophiostoma bicolor is one of the dominant species of the mycobiota associated with Ips genus bark beetles which infect the spruce trees across the Eurasian continent. Host spruce trees resist fungal invasion through structural and inducible defenses, but the underlying mechanisms at the molecular level, particularly with respect to the interaction between bark beetle-associated fungi and host trees, remain unclear. The aim of this study was to observe the pathological physiology and molecular changes in Picea koraiensis seedlings after artificial inoculation with O. bicolor strains (TS, BH, QH, MX, and LWQ). This study showed that O. bicolor was a weakly virulent pathogen of spruce, and that the virulent of the five O. bicolor strains showed differentiation. All O. bicolor strains could induce monoterpene release. A positive correlation between fungal virulence and release of monoterpenes was observed. Furthermore, the release rate of monoterpenoids peaked at 4 dpi and then decreased from 4 to 90 dpi. Transcriptomic analysis at 4 dpi showed that many plant-pathogen interaction processes and mitogen-activated protein kinase (MAPK) metabolic processes were activated. The expression of monoterpene precursor synthesis genes and diterpenoid synthesis genes was upregulated, indicating that gene expression regulated the release rate of monoterpenes at 4 dpi. The enriched pathways may reveal the immune response mechanism of spruce to ophiostomatoid fungi. The dominant O. bicolor possibly induces the host defense rather than defense depletion, which is likely the pattern conducted by the pioneers of beetle-associated mycobiota, such as Endoconidiophora spp. Overall, these results facilitate a better understanding of the interaction mechanism between the dominant association of beetles and the host at the molecular level.